42nd International Conference on Organizational Science Development: Interdisciplinarity Counts (University of Maribor Press, 2023)
The 42nd International Scientific Conference on the Development of Organisational Science was held in Portorož from the 22nd to the 24th of March 2023. The main aim of the conference was to promote the importance of knowledge from an interdisciplinary perspective through academic and scientific debates and professional developments from the economic and non-economic worlds. The conference, which was held under the umbrella title "Interdisciplinarity Counts", aimed to emphasize the importance of the knowledge and competencies of the national and international environment, which enable better and more comprehensive development of individuals, organizations, and society. Changes in all environments dictate a broader perception of the interconnectivity of knowledge and competencies from different scientific and applied fields as a pillar of the development dimension. It is undoubtedly more important than ever to take decisions that generate synergies between innovation, different sciences, and applied approaches, and to promote changes in business models that will lead to a sustainable and socially responsible development environment. In Portorož, we have reconnected opinions, views, and scientific and professional debates that will stimulate all of us to act in the future, both in organizations and in society at large.